DESENTRALISASI IRIGASI: STUDI KASUS PENGELOLAAN IRIGASI DI DAERAH IRIGASI TAJUM KABUPATEN BANYUMAS DECENTRALIZATION IN THE IRRIGATION SECTOR: A CASE STUDY ON IRRIGATION MANAGEMENT IN TAJUM IRRIGATION AREA, BANYUMAS REGENCY - Harsanto, Bambang Tri; , Simin (Pembangunan Pedesaan, 2006)
This research aimed at finding out the role of local government in facilitating irrigation management held by P3A and identifying factors determining P3A in irrigation management. Results of the research showed that (1) the role of local government in facilitating the management was undertaken by providing supervision to P3A. Supervisions were included institutionalization, financial, and technical assistance, (2) supervision was not said successful yet in good manners since there were the following obstacles: (a) technical, (b) knowledge, and (c) institutional obstacles. (3) the role of P3A in the management was undertaken in irrigation infrastructure and water distribution activities. However, such a role had not been generated optimal benefits for making P3A autonomy in overcoming arising conflicts among its members. and (4) factors of P3A development were determined by P3A capability in organizational management as an internal factor, and effects of natural condition, population, and market pressures, and government intervention as external factors.